Long-term implications of pacemaker insertion in younger adults: a single centre experience. (14th October 2021) - Shirwaiker, A; William, J; Mariani, J; Kistler, P; Patel, H; Voskoboinik, A
Abstract: Background: The long-term implications of pacemaker insertion in younger adults are poorly described in the literature. Methods: We performed a retrospective analysis of consecutive younger adult patients (18–50 years) undergoing pacemaker implantation at a quaternary hospital between 1986–2020. Defibrillators and cardiac resynchronisation therapy devices were excluded. All clinical records, pacemaker checks and echocardiograms were reviewed. Results: 81 patients (39.5±9.6 years, 53% male) underwent pacemaker implantation. Indications were complete heart block (41%), sinus node dysfunction (33%), high grade AV block (11%) and tachycardia-bradycardia syndrome (7%). During a median 7.6 (IQR=0.6–14.8) years follow-up, 9 patients (11%) developed 13 late device-related complications (generator or lead malfunction requiring reoperation (n=11), device infection (n=1) and pocket revision (n=1)). Five of these patients were <40 years old at time of pacemaker insertion. At long-term follow-up, a further 9 patients (11%) experienced significant symptoms from inadequate lead performance managed with device reprogramming. Sustained ventricular tachycardia was detected in 2 patients (2%). Deterioration in ventricular function (LVEF decline >10%) was observed in 14 patients (17%) and 7 of these patients required subsequent biventricular upgrade. Furthermore, 4 patients (5%) developed new tricuspid regurgitation (≥ moderate-severe). Of 69 patients with available long-term pacing data, minimal pacemaker utilisation (pacing <5% at all checks) was observed in 13 (19%) patients. Conclusions: Pacemaker insertion in younger adults has significant long-term implications. Clinicians should carefully consider pacemaker insertion in this cohort given risk of device-related complications, potential for device under-utilisation and issues related to lead longevity. In addition, patients require close follow-up for development of structural abnormalities and arrhythmias. Funding Acknowledgement: Type of funding sources: None.